Grounded Theory as a Qualitative Research Method (Journal of Vishwa Adarsha College, 2025)
Grounded theory is a qualitative research method. It is growing in popularity for its use in scholarly research works that demand scientific yet flexible study. However, early career researchers often get confused about the theory’s proceedings. They are also overwhelmed by the immense data collected in different forms from various sources. This paper explores the grounded theory as a qualitative method along with its definition, essential characteristics, advantages, and disadvantages. Based on the reviews on some available representative literatures, this study analyzes the discourses available on the grounded theory method and explores its constructivist approach in particular and the classical and interpretive grounded theories in general. The findings reveal that grounded theory, especially the constructivist grounded theory with all its essentials, is an emerging qualitative research method having many merits and demerits for the researchers.